Imaging of fluorescent polymer dots in relation to channels and immune cells in the lymphatic system - Yufan Zhang; Juxiang Zhang; Xiaowei Li; Jingru Li; Shuting Lu; Yuqiao Li; Panting Ren; Chunfu Zhang; Liqin Xiong (Materials Today Bio, 2022)
Polymer dots (Pdots) have been applied to imaging lymph nodes (LNs) and lymphatic vessels (LVs) in living mice and rats. However, the mechanism of absorption, distribution, metabolism, and excretion of Pdots in LNs and LVs is still unclear. Therefore, the relationship between Pdots and immune cells, LVs and collagen fibers in lymphatics was studied by multiple in vivo and ex vivo microscopic imaging methods and detection techniques. Flow cytometry showed that Pdots could be phagocytosed by macrophages and monocytes, and had no relationship with B cells, T cells and dendric cells in LNs. Silver staining, immunofluorescence and two-photon microscope showed that Pdots gathered in collagen fibers and LVs of LNs. Furthermore, immunofluorescence imaging results verified that Pdots were distributed in the extracellular space of collecting LVs endothelial cells. In addition, Pdots in the collecting LVs were basically cleared by leaking into the surrounding tissue or draining LNs after 21 days of injection. During the long-time observation, Pdots also helped monitor the contraction frequency and variation range of LV. Our study lays a foundation on the research of Pdots as the carrier to study lymphatic structure and function in the future.